The Impact of Lifestyle Branding on the Customers’ Emotions towards the Brand - Lech, Dominika (Wpływ marki opartej na stylu życia na emocje konsumentów do marki, 2023)
With the constantly growing needs of consumers, lifestyle brands were able to gain the recognition of many of those. Such brands are distinguished by their constant aim for understanding their consumers and creating meaningful relationships. The issue of lifestyle branding has not received considerable critical attention within marketing textbooks and academic journals, nonetheless it is a widely examined subject in magazines and books on societal issues. The aim of this article was to shine new light on this subject through an examination of the relations between lifestyle branding and consumers’ emotions towards the brand. The data for this study were collected using quantitative analysis. The methodological approach taken in this study is based on actual experimental research, based on a questionnaire predetermined by the “consumers’ emotional attachments to brands” scale. It aimed at determining a causal relationship between the following variables: independent variable, namely the lifestyle content in the fictional brand advertisement, and dependent variables, such as brand affection, passion, and connection.
s. 90-105
Keywords: branding; lifestyle branding; customers' emotions; multiple-case research; true experimental design; marka oparta na stylu życia; emocje konsumentów; analiza jakościowa; studia przypadków; eksperymentalne badanie